EFEKTIVITAS LATIHAN CORE STABILITY DALAM MENINGKATKAN KESEIMBANGAN DAN POSTUR TUBUH PADA PEKERJA KANTORAN - Nurshal, Rezki Amalia; Marliana; Ilham, Faiz (Journal of Hospital Administration and Management (JHAM), 2023)
Office workers often experience balance and posture issues due to prolonged sitting habits. Core stability exercises are one of the methods that can be used to improve balance and correct posture. This study aims to analyze the effectiveness of core stability exercises in enhancing balance and posture among office workers. The research method used was an experimental design with a pre-test and post-test approach in the intervention group. The study sample consisted of office workers experiencing balance and posture issues. The intervention involved core stability exercises conducted over a specific period. Balance was measured using the Berg Balance Scale (BBS), while posture was assessed through postural observation methods. The study results showed a significant improvement in balance and posture after the core stability exercise intervention (p < 0.05). This indicates that core stability exercises are effective in improving balance and posture in office workers. Therefore, this exercise can be recommended as a strategy to reduce the risk of musculoskeletal disorders caused by static work patterns.